The Influence of Souvenir Authenticity, Satisfaction and Co -Creation of Experience to Place Attachment with Memorable Shopping Experience (Survey on tourist shopping rendang souvenirs in Payakumbuh) - Hasra Hijratul Adha; Verinita Verinita; Eri Besra (Enrichment : Journal of Management, 2022)
This study aims to see the influence of souvenir authenticity, satisfaction and co-creation of experience on place attachment with memorable shopping experiences for tourists who buy rendang souvenirs in Payakumbuh city. The population is all tourists who visit and buy rendang in Payakumbuh city. The sample criteria are respondents who have visited Payakumbuh city and purchased rendang within the last 6 months. The number of samples in the study 160 respondents. Hypothesis testing using statistical analysis with one tailed. The hypothesis is accepted if the t-statistic value is > 1,65 and the significance value is < 0,05. The results show that souvenir authenticity and satisfaction have an influence on place attachment. Meanwhile, co-creation has no effect on place attachment. Souvenir authenticity, satisfaction and co-creation of experience have an influence on a memorable shopping experience and memorable shopping experience have an influence on place attachment.